Measurement of local fluid levels and oscillation frequency on the reconstructed hydrodynamic table - Petříková M.; Kryštůfek P. (EPJ Web of Conferences, 2014)
The article deals with more accurate measurement of the hydrodynamic table. More accurate measurements can be realized thanks to the unique traversal device and sensor water level. Measurements can be pointwise, which was not possible until now.